Solubility and Dissolution Enhancement of Ebastine by Surface Solid Dispersion Technique - Lina S. Hussein; Eman B. H. Al-Khedairy (Iraqi Journal of Pharmaceutical Sciences, 2021)
Ebastine (EBS) is a non-sedating antihistamine with a long duration of action. This drug has predominantly hydrophobic property causing a low solubility and low bioavailability. Surface solid dispersions (SSD) is an effective technique for improving the solubility and dissolution rate of poorly soluble drugs by using hydrophilic water insoluble carriers.